Validation strategies for antibodies targeting modified ribonucleotides - Weichmann, Franziska; Dieterich, Christoph; Hett, Robert; Schepers, Aloys; Ito-Kureha, Taku; Flatley, Andrew; Slama, Kaouthar; Hastert, Florian D; Angstman, Nicholas B; Cardoso, M Cristina; König, Julian; Hüttelmaier, Stefan; et al. (RNA)
Chemical modifications are found on almost all RNAs and affect their coding and noncoding functions. The identification of m6A on mRNA and its important role in gene regulation stimulated the field to investigate whether additional modifications are present on mRNAs. Indeed, modifications including m1A, m5C, m7G, 2′-OMe, and Ψ were detected. However, since their abundances are low and tools used for their corroboration are often not well characterized, their physiological relevance remains largely elusive. Antibodies targeting modified nucleotides are often used but have limitations such as low affinity or specificity. Moreover, they are not always well characterized and due to the low abundance of the modification, particularly on mRNAs, generated data sets might resemble noise rather than specific modification patterns. Therefore, it is critical that the affinity and specificity is rigorously tested using complementary approaches. Here, we provide an experimental toolbox that allows for testing antibody performance prior to their use.
Gesehen am 22.10.2020